Encyclopedic dictionary of polymers - Gooch, Jan W. (Jan Woodall) 1946- (Springer reference, 2007)
Contains numerous polymeric material terms, including the names of chemicals, processes, formulae, and analytical methods that are used frequently in the polymer and engineering fields.